Students’ Perceptions of YouTube Videos To Enhance English Vocabulary - Alqaromah, Maylan; Setiani, Rulik (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2026)
The integration of digital media into language learning has transformed the way students acquire English vocabulary beyond the classroom, with YouTube emerging as a widely used platform that provides rich audiovisual content supporting vocabulary development. Despite its popularity, understanding of how students perceive and utilize YouTube as a learning medium remains limited. This study employed a qualitative descriptive approach to explore students’ perceptions of using YouTube videos to enhance English vocabulary, focusing on cognitive, affective, and conative aspects. Twenty-three undergraduate students from the English Education Study Program participated in the preliminary stage, and fourteen who met the criteria were selected for in depth interviews through purposive sampling. Data were collected using semi structured interviews and analysed thematically to identify patterns in students’ experiences. The findings reveal that YouTube facilitates contextual vocabulary comprehension in the cognitive aspect, enhances motivation and enjoyment that strengthen engagement in the affective aspect, and fosters independent learning behaviours such as replaying videos, using subtitles, and taking notes in the conative aspect. Challenges remain, including inconsistent study habits, reliance on personal interests, and potential distractions. In conclusion, YouTube holds strong potential as a medium for vocabulary learning, yet its effectiveness depends on structured and strategic use to optimize benefits.